HIV/AIDS, growth and poverty in KwaZulu-Natal and South Africa: An integrated survey, demographic and economy-wide analysis - Thurlow, James; Gow, Jeff; George, Gavin (Wiley, 2009)
This paper estimates the economic impact of HIV/AIDS on the KwaZulu‐Natal province and the rest of South Africa.We extended previous studies by employing: an integrated analytical framework that combined firm surveys of workers' HIV prevalence by sector and occupation; a demographic model that produced both population and workforce projections; and a regionalized economy‐wide model linked to a survey‐based micro‐simulation module. This framework permits a full macro‐microeconomic assessment.Results indicate that HIV/AIDS greatly reduces annual economic growth, mainly by lowering the long‐run rate of technical change. However, impacts on income poverty are small, and inequality is reduced by HIV/AIDS. This is because high unemployment among low‐income households minimises the economic costs of increased mortality. By contrast, slower economic growth hurts higher income households despite lower HIV prevalence.We conclude that the increase in economic growth that results from addressing HIV/AIDS is sufficient to offset the population pressure placed on income poverty. Moreover, incentives to mitigate HIV/AIDS lie not only with poorer infected households, but also with uninfected higher income households.Our findings reveal the substantial burden that HIV/AIDS places on future economic development in KwaZulu‐Natal and South Africa, and confirms the need for policies to curb the economic costs of the pandemic.